Serotonin in Parkinson's disease - Kohl, Zacharias; Winkler, Jürgen (Handbook of Behavioral Neuroscience, 2020)
Motor symptoms in Parkinson's disease (PD) are tightly linked to the degeneration of substantia nigra dopaminergic neurons and their projections into the striatum leading to the prototypical motor manifestations of the disease. However, the affection of various other neurotransmitters accounts for a large variety of motor as well as nonmotor symptoms in PD. The loss of serotonergic neurons and alterations of their projections into corresponding targets play an important role in a broad range of motor as well as nonmotor symptoms, including tremor, fluctuations of motor function, cognition, depression, anxiety, and psychosis. Here, we highlight current findings from neuropathological studies as well as animal models of PD, and relate them to recent clinical imaging results, underlining the importance of a compromised serotonergic system in PD and address potential future treatment strategies.
CRIS-Team Scopus Importer:2020-01-31
Keywords: 5-HT; Alpha-synuclein; Hippocampus; Hyperinnervation; Parkinson's disease; Serotonin receptor; Striatum; Synaptic loss